Identità instabili Vivere in una società incandescente - VISENTIN, MARTINA (Vite parallele, Ibridazioni e Società Mutagena - Open Access, 2019)
Rapid changes are transforming the world and some of these represent the guiding thread of this volume. Unpredictable, dramatic consequences may occur if effective measures are not put in place. Measures that can reverse the destructive course that contemporary civilization is following and with which we are undermining the conditions of existence of that same civilization. By addressing various topics ranging from the cultural construction of modern Norway to the issue of ideological overheating up to young people, the challenge of this volume is to offer a profound reflection on our society.